Annexin A7 is a critical regulator of Ca2+ mobilization and lipid metabolism during platelet activation and arterial thrombosis. (25th November 2020) - Borst, O; Geue, S; Manke, M.C; Peng, B; Muenzer, P; Kollotzek, F; Lang, F; Duerschmied, D; Ahrends, R; Gawaz, M
Abstract: Background: Platelet activation after contact to subendothelial collagen following atherosclerotic plaque rupture can lead to arterial thrombosis with acute thrombotic vascular occlusion. Annexin A7 (AnxA7) is an intracellular Ca2+- and phospholipid-binding protein that participates in the regulation of prostaglandin production in inflammatory diseases, but also in cell survival and tumor growth. Objective: In the present study, we aimed to determine the role of AnxA7 for platelet Ca2+ signaling and lipid metabolism in platelet activation and arterial thrombosis in gene-targeted mice lacking annexin A7 (Anxa7−/−). Results: AnxA7 is strongly expressed in platelets of platelet-rich human coronary thrombi aspirated from patients with acute ST elevation myocardial infarction. Functionally, platelet aggregation and dense granule secretion were significantly abrogated in Anxa7−/− platelets as compared to wildtype platelets (Anxa7+/+) after activation with collagen or collagen-related peptide (CRP), a specific agonist of the major platelet collagen receptor glycoprotein VI (GPVI). Further, in vitro thrombus formation on a collagen-coated surface under high arterial shear rates was significantly diminished in Anxa7-deficient platelets, and thrombotic vascular occlusion after FeCl3-induced injury in vivo was blunted in Anxa7−/−bone marrow chimeric mice, but no prolongation of bleeding time was observed. Moreover, Anxa7−/− platelets showed a significant reduction of IP3 production due to an abolished phospholipase C (PLC) gamma2 phosphorylation resulting in an abolished increase of [Ca2+]i after platelet activation with CRP. Moreover, we could show by quantitative lipidomics analysis that annexin A7 critically affects platelet oxylipid metabolism following activation of GPVI-dependent platelet signalling since Anxa7−/− platelets showed a significant reduction of the bioactive metabolites thromboxane A2 and 12(S)-hydroxy-eicosatetraenoic acid (12(S)-HETE) levels as well as significantly reduced levels of several other prostaglandins following stimulation with collagen or CRP. Finally, defective PLCgamma2 phosphorylation, IP1 production and blunted increase of [Ca2+]i in Anxa7−/− platelets could be rescued by exogenous addition of 12(S)-HETE indicating that AnxA7 is a critical regulator of the platelet oxygenase 12-lipoxygenase (12-LOX) in GPVI-dependent platelet Ca2+ signalling during arterial thrombosis following activation by collagen. Conclusions: The present study reveals annexin A7 as a critical regulator of oxylipid metabolism and Ca2+ signaling in GPVI-dependent platelet activation. Anxa7-deficiency further results in decreased in vitro and in vivo thrombus formation, but does not affect bleeding time. In conclusion, annexin A7 plays an important role in platelet signaling during arterial thrombosis and thus, may reflect a promising target for novel antiplatelet strategies. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German Research Foundation (Deutsche Forschungsgemeinschaft, DFG)